تقييم الصحفيين اليمنيين لتغطية الصحافة اليمنية لمؤتمر الحوار وقضاياه - العمار, علي حسين; علي الشاوري, عبد الرحيم (Sciences de l'Homme et de la Société, 2016)
هدفت هذه الدراسة إلى تقييم الصحفيين اليمنيين لتغطية الصحافة اليمنية لمؤتمر الحوار الوطني وقضاياه من خلال متابعتها لهذه التغطية واعتمادها على الصحف كمصادر أساسية للحصول على المعلومات عن مؤتمر الحوار وقضايا، بالإضافة إلى معرفة مدى حيادية هذه الصحف عند تغطيتها لمؤتمر الحوار ناهيك عن التعرف على المشكلات والصعوبات والعقبات التي واجهت الصحفيين أثناء تغطيتهم لمؤتمر الحوار الوطني وقضاياه.     Abstract : This study aimed to assess the Yemeni journalists to cover the Yemeni press of the Conference of National Dialogue and its issues through follow-up to this coverage and reliance on newspapers as sources essential to get information about the issues Dialogue Conference, as well as to see how the neutrality of these newspapers when the coverage of the Conference of the dialogue, let alone to identify the problems and the difficulties and obstacles faced by journalists during their coverage of the Conference of National dialogue and issues.